Physcion ameliorates pancreatic β-cell dysfunction and diabetes-related oxidative stress markers in type 2 diabetes rat model - Alonyenu Edwin Inalegwu; Idowu Asegame Aimola; Aminu Mohammed (Elsevier, 2021)
Background: Physcion is an active component of Rheum officinale Baill, a popular traditional Chinese medicine used locally to treat diabetes. Previous studies revealed that physcion possessed antidiabetic activity of physcion using various in vitro models and no information is available on the antidiabetic activity of physcion in animal model. Therefore, the present study aimed to investigate the antidiabetic effect of physcion in fructose-fed streptozotocin (STZ)-induced type 2 diabetes (T2D) rat model. In addition, acute toxicity of the physcion was evaluated in Wistar rats. Methods: Physcion was administered orally at 10, 20 30 mg/kg body weight (bw) for four (4) weeks to the treated animals. Acute exposure of physcion was used to notice any sign of toxicity in the treated animals. Results: Acute exposure of physcion showed no noticeable sign of toxicity in the treated animals. The diabetic untreated animals showed significant (P< 0.05) high fasting blood glucose (FBG), insulin resistance, dyslipidemia, inflammation and alterations in oxidative stress biomarkers. Oral administration of physcion (P< 0.05) improved the alterations induced by diabetes comparable to metformin treated group. Conclusion: This study therefore, confirms the antidiabetic activity of physcion in animal model and recommends for further clinical study to verify the antidiabetic effect in human subjects.